Neural Responses to Physical Characteristics of a High Velocity, Low Amplitude Spinal Manipulation: Effect of Thrust Direction - Reed, William R. (Spine (Phila Pa 1976), 2018)
STUDY DESIGN: Electrophysiological recordings were obtained from proprioceptors in deep lumbar paraspinal muscles of anesthetized cats during high velocity low amplitude spinal manipulation (HVLA-SM). OBJECTIVE: To determine how thrust direction of an HVLA-SM affects neural input from back musculature. SUMMARY OF BACKGROUND DATA: A clinician's ability to apply the thrust of an HVLA-SM in a specified direction is considered an important component of its optimal delivery. However, previous biomechanical studies indicate that the shear force component of the thrust vector is not actually transmitted to paraspinal tissues deep to the thoracolumbar fascia because the skin-fascia interface is frictionless. METHODS: Neural activity from muscle spindles in the multifidus and longissimus muscles were recorded from L(6) dorsal rootlets in 18 anesthetized cats. Following preload to the spinal tissues, HVLA-SMs (100ms thrust duration) were applied through the intact skin overlying the L(6) lamina. Thrusts were applied with at angles oriented perpendicularly to the back and obliquely at 15° and 30° medialward or cranialward using a 6×6 Latin square design with 3 replicates. The normal force component was kept constant at 21.3N. HVLA-SMs were preceded and followed by simulated spinal movement applied to the L(6) vertebra. Changes in mean instantaneous discharge frequency (ΔMIF) of muscle spindles were determined during the thrust and during spinal movement. RESULTS: ΔMIFs during the HVLA-SM were significantly greater in response to all thrust directions compared to the preload alone but there was no difference in ΔMIF for any of the thrust directions during the HVLA-SM. HVLA-SM decreased some of the responses to simulated spinal movement but thrust direction had no effect on these changes. CONCLUSIONS: The shear force component of an HVLA-SM's thrust vector is not transmitted to the underlying vertebra sufficient to activate muscle spindles of the attached muscles. Implications for clinical practice and clinical research are discussed.